The Marginal and Average Propensities to Consume - Hubbard, Joshua C. (Quarterly Journal of Economics, 1954)
I. The weakness of existing theories, 83. — II. An alternative theoretical model, 85. — III. Synthesis and a comparison with the facts, 91.